An original method of analysis of the breast contour curve with 3-dimensional imaging: Case series. Issue 31 (5th August 2022) - Otsuki, Yuki; Ueda, Koichi; Ichida, Tatsuya; Nuri, Takashi; Okada, Masashi
Abstract : Introduction: Postoperative assessment of breast reconstruction results has become increasingly important. In this paper, a unique analysis method with 3-dimensional surface images of patients who were treated with immediate breast reconstruction is presented. Patient concerns: Five Japanese women were suspected of having breast cancer and visited our hospital for treatment. Diagnosis: Breast cancer was diagnosed by biopsy, mammography, ultrasonography, computed tomography, and magnetic resonance imaging. Interventions: Five patients underwent nipple/skin-sparing mastectomy, concomitant sentinel lymph node biopsy, and immediate breast reconstruction in our hospital. Three cases were reconstructed by extended latissimus dorsi flaps, one was reconstructed by a pedicled transverse rectus abdominis myocutaneous flap, and one was reconstructed by a deep inferior epigastric artery perforator flap. Three-dimensional photographs were taken 1 year postoperatively. The similarity of the breast contours between the reconstructed breast and the nonaffected opposite breast obtained from 3-dimensional images was analyzed. The calculated value is called the breast contour score. Outcomes: No recurrence was observed during the follow-up period in any cases. All cases could be analyzed by breast contour score to evaluate the breast shapes. Conclusion: The scores become a relative value that ranges from 0 (completely different) to 100 (completely the same). By expressing the score as a relative value, the breast contour score could help us understand the degree of breast symmetry more intuitively.